AB0556 Monocyte Chemoattractant Protein-1 in Systemic Lupus Erythematosus. (10th June 2014) - Zivkovic, V.G.; Deljanin Ilić, M.; Stankovic, A.; Cvetkovic, T.; Mitic, B.; Stamenkovic, B.; Nedovic, J.; Milenkovic, S.; Stojanovic, S.
Abstract : Background: In recent years, potential biological markers of systemic lupus erythematosus (SLE) and LN activity have been intensely sought for. Among them, it seems that monocyte chemoattractant protein-1 (MCP-1) has a prominent place as a marker of LN activity. Objectives: Our aim in this paper was to investigate the level of MCP-1 in the serum and urine of SLE patients and to establish its correlation with SLE and LN activity. Methods: The study involved 72 patients with SLE, hospitalized in the Rheumatology Clinic, Institute "Niška Banja", during 2011, in whom the diagnose was made using the criteria of the ARA revised in 1997, 27 with LN and 45 without signs of LN, as well as 30 healthy individuals. The Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) was used to assess the disease activity. In addition to other standard laboratory and immunological analyses, the level of MCP-1 was determined in SLE patients and controls in their serum and urine samples using the sandwich enzyme immunosorbent assay method, in accordance with the manufacturer's directions (R&D Systems, Inc. Minneapolis, USA). Results: The examinees in the investigated group were aged 46.4±9.3 years on the average. Average age of control subjects was 44.7±9.5 years. In SLE group there were 66 (91.7%) women and 6 (8.3%) men, and in control group 27 (90%) women and 3 (10%) men. Average disease duration in the studied group was 11.2±8.1 years. Average SLEDAI value was 10.9±6.9, with a median of 8. Our investigation showed that mean MCP-1 values in the sera of SLE patients were significantly higher compared to average values in controls (728.7±879.7 pg/ml vs. 225.9±42.0 pg/ml; p<0.001). Mean values of MCP-1 in the urine of SLE patients were also significantly higher, regardless of disease activity, renal involvement, and treatment used, compared to healthy controls (179.2±181.5 pg/ml vs. 94.7±31.6 pg/ml; p<0.01). For the cut-off of >266.7 pg/ml the specificity and sensitivity of serum MCP-1 for SLE diagnosis was 90% and 77.8% respectively (95% CI 0.817-0.946; AUC 0.894), and for the cut-off of >166.0 pg/ml the specificity and sensitivity of urine MCP-1 was 100% and 44.4% respectively (95% CI 0.588-0.776; AUC 0.688). Our results demonstrated that the urinary and not serum MCP-1 was in a positive correlation with proteinuria (r=0.839; p<0.001) and in negative correlation with glomerular filtration assessed using the Modification of Diet in Renal Disease (MDRD) formula (r=-0.293; p<0.05). Both serum and urinary MCP-1 demonstrated a positive correlation with SLEDAI (r=0.318; p<0.01 and r=0.431; p<0.001). Conclusions: Serum and urine MCP-1 can be an indicant of global SLE activity. Urine MCP-1 can be a marker of LN activity, since it is in correlation with renal damage and function parameters – in a positive correlation with proteinuria, and in negative one with glomerular filtration. Future longitudinal studies of this cytokine in a larger number of SLE patients could perhaps provide us with some conclusive answers about the significance of MCP-1 determination in early detection of subclinical forms of LN, predictions of disease relapses, and timely treatment of SLE patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.3854